Investigation of Various Properties for Zirconium Oxide Films Synthesized by Sputtering. (2016) - Patel, Uttkarsh S.; Patel, Kartik H.; Chauhan, Kamlesh V.; Chawla, Amit Kumar; Rawal, Sushant K.
Abstract: The aim of this paper is to deposit zirconium oxide films by magnetron sputtering process at different argon partial pressure values of 45%, 55%, 62% and 67%. The effect of argon partial pressure on structural, optical and wettability properties of zirconium oxide films is investigated in this research work. The increase in argon partial pressure leads to increase in intensity of (111) peak for zirconium oxide thin films as observed by X-ray Diffraction. The average crystallite size of zirconium oxide films increases from 19 nm to 25 nm with increase in argon partial pressure. Wettability properties of zirconium oxide films such as contact angle and surface energy were determined by contact angle measuring system. The minimum transmission values above 63% were observed for all zirconium oxide thin films deposited at different argon partial pressure. Band gap and refractive index of zirconium oxide thin films varies as a function of argon partial pressure.